(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
This study outlines the current state and norms of the Hungarian public education in the light of the results of the latest PISA surveys. It highlights that Hungarian students are considerably behind in all aspects of the subject areas, which means that their knowledge in mathematics, reading comprehension and scientific studies needs to catch up with the average level of other OECD member countries. This review also examines the financial support of the Hungarian public education and reveals that not only is the standard of public education considerably lower in Hungary, but it is also underfinanced compared to other OECD countries. A number of earlier studies have emphasised that the quality of education depends predominantly on the performance of the individual teachers and not on class size, number of lessons or on how well the classroom is equipped. The motivation of teachers is therefore vitally important, however, the previous wage schedule for public sector employees is inadequate for this purpose. One of the main objectives of the Act CXC of 2011 on Public Education is to implement a new career model and promotion system for teachers, which has fundamentally reformed HR in the area of pedagogy.